Practical Considerations for Use of Direct Oral Anticoagulants in Children - Whitworth, Hilary; Raffini, Leslie (Frontiers in Pediatrics, 2022)
Direct oral anticoagulants (DOACs) provide an attractive alternative for the management and prevention of thrombosis in pediatric patients. With multiple ongoing and published pediatric trials and recent regulatory approval of dabigatran and rivaroxaban, the landscape of pediatric anticoagulation is rapidly changing. However, as pediatricians gain experience with these drugs, it is important to be mindful of pediatric-specific considerations that may limit the use of DOACs in certain children and adolescents. While there is increasing adult data and experience, there is a paucity of real-world evidence to guide the use of these drugs in children who would not have met clinical trial inclusion criteria. In this mini review, we summarize pediatric specific data, areas for future research, and practical considerations for the use of DOACs in children and adolescents.